Ali pogodbeno delo izven delovnega razmerja uživa kazenskopravno varstvo? - Polajžar, Aljoša (Delavci in delodajalci, 2022)
The authors analyse the question whether criminal law protection in the context of criminal offenses against the employment relationship (Articles 196 and 197 of KZ-1) is also granted to persons who perform personal contractual work for others outside the employment relationship. The authors note that (in the light of the principle of legality) the protection under Articles 196 and 197 of KZ-1 applies only to workers in an employment relationship. De lege ferenda, a certain amendment of the criminal offenses against the employment relationship would be justified in order to ensure that certain criminal protection would be provided (with sufficient clarity) to other contractors outside the employment relationship.
Keywords: civil law forms of work; criminal acts against employment relationship; delovna razmerja; employment relationships; kazensko pravo; kazniva dejanja; mobing; notion of a worker; pogodbeno delo; šikaniranje; the principle of legality in criminal law; workplace harassment